Transcriptomic dissection of Bradyrhizobium sp. strain ORS285 in symbiosis with Aeschynomene spp. inducing different bacteroid morphotypes with contrasted symbiotic efficiency - Florian Lamouche; Djamel Gully; Anaïs Chaumeret; Nico Nouwen; Camille Verly; Olivier Pierre; Coline Sciallano; Joël Fardoux; Christian Jeudy; Attila Szücs; Samuel Mondy; Christophe Salon; et al. (Environmental Microbiology, 2019)
Summary To circumvent the paucity of nitrogen sources in the soil legume plants establish a symbiotic interaction with nitrogen‐fixing soil bacteria called rhizobia. During symbiosis, the plants form root organs called nodules, where bacteria are housed intracellularly and become active nitrogen fixers known as bacteroids. Depending on their host plant, bacteroids can adopt different morphotypes, being either unmodified (U), elongated (E) or spherical (S). E‐ and S‐type bacteroids undergo a terminal differentiation leading to irreversible morphological changes and DNA endoreduplication. Previous studies suggest that differentiated bacteroids display an increased symbiotic efficiency (E > U and S > U). In this study, we used a combination of Aeschynomene species inducing E‐ or S‐type bacteroids in symbiosis with Bradyrhizobium sp. ORS285 to show that S‐type bacteroids present a better symbiotic efficiency than E‐type bacteroids. We performed a transcriptomic analysis on E‐ and S‐type bacteroids formed by Aeschynomene afraspera and Aeschynomene indica nodules and identified the bacterial functions activated in bacteroids and specific to each bacteroid type. Extending the expression analysis in E‐ and S‐type bacteroids in other Aeschynomene species by qRT‐PCR on selected genes from the transcriptome analysis narrowed down the set of bacteroid morphotype‐specific genes. Functional analysis of a selected subset of 31 bacteroid‐induced or morphotype‐specific genes revealed no symbiotic phenotypes in the mutants. This highlights the robustness of the symbiotic program but could also indicate that the bacterial response to the plant environment is partially anticipatory or even maladaptive. Our analysis confirms the correlation between differentiation and efficiency of the bacteroids and provides a framework for the identification of bacterial functions that affect the efficiency of bacteroids.© 2018 Society for Applied Microbiology and John Wiley & Sons Ltd

S inorhizobium fredii HH 103 bacteroids are not terminally differentiated and show altered O ‐antigen in nodules of the Inverted Repeat‐Lacking Clade legume G lycyrrhiza uralensis - Juan C. Crespo‐Rivas; Ibtissem Guefrachi; Kenny C. Mok; José A. Villaécija‐Aguilar; Sebastián Acosta‐Jurado; Olivier Pierre; José E. Ruiz‐Sainz; Michiko E. Taga; Peter Mergaert; José M. Vinardell (Environmental Microbiology, 2016)
Summary In rhizobial species that nodulate inverted repeat‐lacking clade ( IRLC ) legumes, such as the interaction between S inorhizobium meliloti and M edicago , bacteroid differentiation is driven by an endoreduplication event that is induced by host nodule‐specific cysteine rich ( NCR ) antimicrobial peptides and requires the participation of the bacterial protein BacA . We have studied bacteroid differentiation of S inorhizobium fredii HH 103 in three host plants: G lycine max , C ajanus cajan and the IRLC legume G lycyrrhiza uralensis . Flow cytometry, microscopy analyses and viability studies of bacteroids as well as confocal microscopy studies carried out in nodules showed that S . fredii HH103 bacteroids, regardless of the host plant, had deoxyribonucleic acid (DNA) contents, cellular sizes and survival rates similar to those of free‐living bacteria. Contrary to S . meliloti , S . fredii HH 103 showed little or no sensitivity to M edicago NCR 247 and NCR 335 peptides. Inactivation of S . fredii HH 103 bac A neither affected symbiosis with G lycyrrhiza nor increased bacterial sensitivity to M edicago NCRs . Finally, HH 103 bacteroids isolated from G lycyrrhiza , but not those isolated from C ajanus or G lycine , showed an altered lipopolysaccharide. Our studies indicate that , in contrast to the S . meliloti ‐ M edicago model symbiosis, bacteroids in the S . fredii HH 103‐ G lycyrrhiza symbiosis do not undergo NCR ‐induced and bac A ‐dependent terminal differentiation.

Transcriptome analysis of a bacterially induced basal and hypersensitive response of Medicago truncatula - Zoltán Bozsó; Nicolas Maunoury; Agnes Szatmari; Peter Mergaert; Péter G. Ott; László R. Zsíros; Erika Szabó; Éva Kondorosi; Zoltán Klement (Plant Molecular Biology, 2009)